VBA developer's handbook - Getz, Ken (Sybex, 2000)
Developers using VBA for programming Microsoft Office and other applications can build customized applications that go far beyond what is possible with simple macros. Written by Mike Gilbert, a key VBA evangelist at Microsoft, and Ken Getz, known to readers around the world for his expertise in Office and Access programming, this revised edition of the best-selling VBA Developer's Handbook introduces programmers to new features of VBA 6. The bonus CD contains all the sample code from the book, with usable solutions to meet more than 300 programming goals with VBA.